2009
DOI: 10.1074/jbc.m806968200
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the Extracellular Matrix Protein WARP Develop Normally but Have Compromised Peripheral Nerve Structure and Function

Abstract: WARP is a recently identified extracellular matrix molecule with restricted expression in permanent cartilages and a distinct subset of basement membranes in peripheral nerves, muscle, and the central nervous system vasculature. WARP interacts with perlecan, and we also demonstrate here that WARP binds type VI collagen, suggesting a function in bridging connective tissue structures. To understand the in vivo function of WARP, we generated a WARPdeficient mouse strain. WARP-null mice were healthy, viable, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…Allen et al (2008) uses a sheep antibody raised against full length recombinant WARP purified from the media of transfected 293-EBNA cells. In that study, WARP was located in the mice vasculature nervous system and in perineural basement membranes, and developing muscle tissue and articular cartilage (Allen 2009). In another study Allen et al used a rabbit polyclonal antisera against VWA domain and C-terminal domains of WARP, using the GST-VWA domain (amino acids 21-212) and the maltose-binding protein-C-terminal domain (amino acids 389-415) fusion proteins, expressed in bacteria as antigens.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Allen et al (2008) uses a sheep antibody raised against full length recombinant WARP purified from the media of transfected 293-EBNA cells. In that study, WARP was located in the mice vasculature nervous system and in perineural basement membranes, and developing muscle tissue and articular cartilage (Allen 2009). In another study Allen et al used a rabbit polyclonal antisera against VWA domain and C-terminal domains of WARP, using the GST-VWA domain (amino acids 21-212) and the maltose-binding protein-C-terminal domain (amino acids 389-415) fusion proteins, expressed in bacteria as antigens.…”
Section: Discussionmentioning
confidence: 94%
“…Allen et al (2008) have suggested that WARP may have an important role in maintaining the blood-brain barrier throughout life. There are only a handful of studies of WARP expression in mice, initially discovered in mouse chondrocytes (Fitzgerald et al, 2002; Allen et al, 2006, 2008, 2009). Further studies on WARP expression showed that WARP is present in the vasculature of neural tissues and in basement membrane structures and cardiac muscle (Allen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations